A Driving Force of Manufacturing Firm Value: Evidence from Vietnam - Minh , Ngo Ngoc; Loc, Nguyen Duc (International Journal of Psychosocial Rehabilitation, 2020)
The paper uses the SPSS 22.0 software and path analysis approach to empirically examine related fundamental factors as profitability and capital structure as mediation to the value of the 89 manufacturing companies listed on the Hanoi Stock Exchange (HNX) in 2011-2019 period. The empirical results of the study prove that profitability has no significant effect on firm value. The capital structure has a positive and significant effect on the value of the company, and at the same time as a mediator. This result is expected to be able to contribute in the form of new policy changes that must be done by the company to increase value.